Study on seismic stability and performance of reinforced soil walls using shaking table tests - Xu, Peng; Hatami, Kianoosh; Jiang, Guanlu (Geotextiles and geomembranes, 2020)
The paper reports a 1 g shaking table test that was carried out on a reinforced soil wall with an objective to study the acceleration amplification in the backfill, and phase differences between dynamic responses of the reinforced and retained zones. Results of the study show that including the observed larger acceleration amplification in the upper half of the wall, and the phase difference between maximum lateral earth pressure and inertial load in the backfill in the analysis would lead to more accurate predictions of: (1) the wall response relative to predicted reinforcement load, (2) elevations of line of action for both the inertial and lateral earth forces in the backfill, and (3) wall deformations, as compared to pseudo-static methods of analysis.